Use of Religion in Blame Avoidance in a Competitive Authoritarian Regime: Turkish Directorate of Religious Affairs (Diyanet) - Yilmaz, Ihsan (Religions, 2022)
Blame avoidance has been one of the most applied strategies by policy makers in both democratic and non-democratic regimes to avoid responsibility and accountability in cases of failure and tragic events. It is also known that politicians have used religion for Machiavellian purposes, as exactly advised by Machiavelli. However, a systematic empirical analysis of how religion is used for blame avoidance by politicians has not been conducted. In this article, we aim to address this gap by examining the empirical data derived from the weekly Friday sermon texts produced by Turkey’s Directorate of Religious Affairs and delivered in more than 90 thousand mosques every week to a large segment of the population in Turkey, where the majority claims to be religious. Starting with its violent response to the peaceful Gezi protests in 2013, the ruling AKP has opened up a new phase in Turkish political history by resorting to civilizational populism: it blamed the Western world for financing and masterminding the protests, using the protestors as internal pawns to attack Turkey and the Muslim World, suppressed the protests brutally and entered into a populist authoritarian regime. Our paper shows, following this turn, how the Diyanet sermons started using religion to help with the AKP’s blame avoidance. The Diyanet either parroted the AKP’s conspiratorial narrative or tried to convince the citizens that all negativities are works of God and with these humans are being tested by God. The AKP’s use of religion to avoid blame is a text-book case of how both a religious institution and religious discourse can be used to help the incumbent avoid responsibility. Whenever, there was a problem that would the AKP votes, the Diyanet’s sermons tried to shift the blame to either God or citizens or conspiratorial enemies.